The Influence of Work Discipline, Motivation and Work Environment on Work Productivity at CV. Construction Consultant: Pengaruh Disiplin kerja, Motivasi dan Lingkungan Kerja terhadap Produktivitas kerja pada CV. Bina Karya Konsultan - Muhammad Rizky Vegas Ramadhan; Hariasih Misti (Academia Open, 2021)
This research aims to determine the influence of work discipline, motivation and work environment on working productivity on CV. Bina Karya Consultant. This research includes quantitative research types with hypothesis testing. The sample was used in this study as much as 57 employees at CV. Bina Karya Consultant. The analytical tools used in this research are the techniques of multiple linear regression test analysis, F test, T test, and multiple determiniation coefficient with the help of software for operating system named SPSS (Statistical Program for social Sience) version 18.0. The primary Data contained in this study was obtained from the questionnaire. The results of this of this study showed that Work Dicipline has significantpositive effect on Work Productivity, Motivation has significant positive effect on Work Productivity, Work Environment has significant positive effect on Work Productivity, Work Dicipline, Motivation and Work Environment simultaneously influence on Work Productivity